Pengaruh Leadership Style, Information System dan Competitive Advantage Pada Bisnis Perhotelan di Jawa Timur - Joanna Edrea Ung; Saarce Elsye Hatane (Business Accounting Review, 2017)
With the development of the tourism industry in East Java, the tourists, both local and foreign come to visit more. Along with these developments, the hospitality industry also is growing in relation to tourism in East Java. As the rapid development of the hospitality industry in East Java, the need to understand more about how to keep the hospitality industry innovation facing its own development in order to provide better service to customers, employees satisfaction and the progress of the hotel itself to appear as leader in the competitive hospitality industry.This study aims to determine the effect of Leadership Style to Competitive advantage through Information system in hotels with 3, 4 and 5 star in East Java. The method used in connection with this research is quantitative. Data obtained by distributing questionnaires to 3, 4 and 5 star hotels in East Java. Respondents in this study were employees of the hotel from several divisions with a minimum 3 years duration of work and minimum positions are as a staff. These results indicate the existence of positive and significant relationship between Leadership style of the Competitive advantage. However, the indirect effect on the relationship of Leadership style adn Competitive Advantage through the Information System has a lower value than the direct effect. It can be concluded that the Information system weakens Leadership style relationship with Competitive advantage.